Persepsi Mahasiswa Akuntansi dan Intensi untuk Menjadi Akuntan yang Profesional dan Berkualitas: Studi Pada Mahasiswa Program Studi Akuntansi Universitas Bhayangkara Jakarta Raya - Mukti, Aloysius Harry; Windiarti, Nabilah Putri; Maharani, Agatha; Nafila, Sevina Ghina; Rizantha, Aditya Muhammad Rafly; Hidayat, Muhammad Faiz (Penerbit Goodwood, 2024)
Purpose: This research aims to study accounting students at Bhayangkara University Jakarta Raya regarding their perceptions of the accounting profession, their level of fortitude, and the need for financial assistance, and whether these factors significantly influence them to become professionally qualified accountants. Methodology/approach: This study was conducted using a questionnaire prepared based on seven independent variables, which were then distributed to accounting students. The sample in this study comprised 65 students from the accounting study program at Universitas Bhayangkara Jakarta Raya. Results: The results showed that salary, prestige or status, opportunities for advancement, and advice received did not affect students' intentions to pursue professional qualifications. At the same time, the variables of job security and stability, financial assistance, and personality fortitude had a significant influence on students’ intention to pursue professional qualifications. Limitation: The number of samplings that do not represent all populations needs to be carefully determined. Contribution: This study contributes to several aspects (1). This was the first study to explore the intentions of students at Universitas Bhayangkara Jakarta Raya (2). This research was a pre-observation of the intention of career pursuit for students in accounting majors.